Laminated nonwoven fabrics and sanitary materials

The laminated nonwoven fabric, featuring specific thermoplastic resin fibers with unique cross-sectional shapes, addresses the challenges of water absorption and quick drying in hygienic materials, achieving enhanced moisture management and comfort.

JP7661879B2Active Publication Date: 2025-04-15TORAY INDUSTRIES INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021513472
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-29
Filing Date
2021-01-18
Publication Date
2025-04-15
Estimated Expiration
2041-01-18

AI Technical Summary

Technical Problem

Existing nonwoven fabrics for hygienic materials face challenges in achieving both rapid water absorption and quick drying properties, due to issues with liquid permeability and capillary effects in current laminated structures.

Method used

A laminated nonwoven fabric is developed, comprising a first thermoplastic resin fiber with a cross-section featuring multiple convex portions and a variable cross-sectional shape, and a second thermoplastic resin fiber with a round cross-section, where the ratio of the average single fiber diameters of the second fiber to the first fiber is 1.0 or more, and the second fiber is laminated on the outermost layer.

Benefits of technology

The laminated nonwoven fabric achieves significant improvements in water absorption speed and quick-drying properties, making it suitable for use in hygienic materials such as diapers and masks, by enhancing moisture diffusion and transfer between layers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661879000003
    Figure 0007661879000003
  • Figure 0007661879000004
    Figure 0007661879000004
  • Figure 0007661879000001
    Figure 0007661879000001
Patent Text Reader

Abstract

The present invention is a layered nonwoven fabric in which at least one each of a nonwoven fabric layer (A) composed of a first thermoplastic resin fiber and a nonwoven fabric layer (B) composed of a second thermoplastic resin fiber are layered, wherein: the cross-section of the first thermoplastic resin fiber has a plurality of lobes, and is a modified cross-section with a lobularity of 5% or more; the ratio (Db / Da) of the average single-fiber diameter Db of the second thermoplastic resin fiber to the average single-fiber diameter Da of the first thermoplastic resin fiber is 1.0 or more; and the nonwoven fabric layer (B) is layered on at least one of the outermost layers. This layered nonwoven fabric has water-absorption speed and water-absorbing / quick-drying properties sufficient to enable the fabric to be utilized as a sanitary nonwoven fabric. By employing this layered nonwoven fabric as at least a portion of a sanitary material, a sanitary material having excellent water absorbability and excellent quick-drying properties can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a different cross-section laminated nonwoven fabric having excellent water absorption and quick drying properties and particularly suitable for use as a sanitary material, and to a sanitary material using the same. [Background technology]

[0002] Generally, sanitary materials such as disposable diapers, sanitary napkins, and masks are made comfortable for the human body by quickly removing moisture such as urine and sweat and keeping the surface of the material dry.

[0003] For this reason, the surface material that comes into direct contact with the skin must be both "absorbent" to quickly absorb moisture and "quick-drying" to transfer the absorbed moisture from the outermost layer and keep the surface dry.

[0004] Conventionally, various nonwoven fabrics that have been hydrophilized have been widely used for this surface material. Although these can guide moisture from the outermost surface layer to the inner nonwoven fabric or absorbent, they tend to retain moisture in the outermost surface layer, making them inferior in "quick-drying properties."

[0005] In order to make the outermost layer less likely to retain moisture and to provide a surface member with excellent "quick-drying properties," Patent Document 1 proposes a nonwoven fabric in which a web layer (skin side) made of fine fibers with a round cross section is laminated with a web layer made of thick fibers with an irregular cross section. Patent Document 2 also proposes a sheet in which sheets with different fiber densities are laminated, with the sheet with the lower fiber density being the surface layer that comes into contact with the skin. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 5-31137 [Patent Document 2] Japanese Patent Application Publication No. 1-20844 Summary of the Invention [Problem to be solved by the invention]

[0007] However, in the technology described in Patent Document 1, the web layer made of fine fibers on the skin side has a dense structure, which reduces liquid permeability and makes it difficult to quickly absorb moisture, making it difficult to achieve "water absorbency." Furthermore, moisture tends to remain in the dense inter-fiber spaces on the fine side, making it difficult to achieve "quick drying."

[0008] On the other hand, the technology described in Patent Document 2 makes it possible to guide a certain amount of moisture absorbed in the outermost layer to the second layer (the layer opposite the skin side) by utilizing the difference in capillary effect that differs depending on the fiber density. However, since the second layer has poor liquid diffusion performance in the sheet surface direction, the migration of moisture to the second layer is limited, and the "quick-drying property" is insufficient.

[0009] SUMMARY OF THE PRESENT EMBODIMENTS Accordingly, an object of the present invention is to provide a laminated nonwoven fabric having a sufficient water absorption rate and quick drying properties to maintain comfort within a member using a nonwoven fabric for sanitary materials. [Means for solving the problem]

[0010] Means for Solving the Problems The present inventors have conducted intensive research to achieve the above object, and as a result have discovered that, by laminating a nonwoven fabric layer made of specific irregular cross-section fibers and a nonwoven fabric layer made of specific size fibers in a specific configuration, it is possible to obtain a laminated nonwoven fabric having sufficient water absorption and quick-drying properties for use as a nonwoven fabric for sanitary purposes.

[0011] The laminated nonwoven fabric of the present invention is a laminated nonwoven fabric in which at least one nonwoven fabric layer (A) made of a first thermoplastic resin fiber and at least one nonwoven fabric layer (B) made of a second thermoplastic resin fiber are laminated, the cross section of the first thermoplastic resin fiber has a plurality of convex portions and is an irregular cross section with a globality of 5.0% or more, the ratio (Db / Da) of the average single fiber diameter Db of the second thermoplastic resin fiber to the average single fiber diameter Da of the first thermoplastic resin fiber is 1.0 or more, and further the nonwoven fabric layer (B) is laminated as at least one of the outermost layers.

[0012] The sanitary material of the present invention is at least partially composed of the above-mentioned laminated nonwoven fabric.

[0013] Furthermore, in the diaper of the present invention, the top sheet is made of the above-mentioned laminated nonwoven fabric.

[0014] In addition, the mask of the present invention has an inner layer made of the laminated nonwoven fabric. Effect of the Invention

[0015] The laminated nonwoven fabric of the present invention has a water absorption rate and water absorption and quick-drying properties sufficient for use as a nonwoven fabric for sanitary materials. By using the laminated nonwoven fabric of the present invention as at least a part of a sanitary material, a sanitary material having excellent water absorption and excellent quick-drying properties can be obtained.

[0016] The laminated nonwoven fabric of the present invention can be used as a part of sanitary materials such as disposable diapers, sanitary napkins, gauze, bandages, masks, gloves, and adhesive bandages. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is an example of a cross section of a first thermoplastic resin fiber constituting the nonwoven fabric layer (A) of the laminated nonwoven fabric of the present invention, and is a diagram illustrating a fiber cross section having a plurality of convex portions. [Diagram 2] FIG. 2 is an example of a cross section of a first thermoplastic resin fiber constituting the nonwoven fabric layer (A) of the laminated nonwoven fabric of the present invention, and is a diagram for explaining the global degree in the fiber cross section. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The laminated nonwoven fabric of the present invention is a laminated nonwoven fabric in which at least one nonwoven fabric layer (A) made of a first thermoplastic resin fiber and at least one nonwoven fabric layer (B) made of a second thermoplastic resin fiber are laminated, the cross section of the first thermoplastic resin fiber has a plurality of convex portions and is an irregular cross section with a globality of 5.0% or more, the ratio (Db / Da) of the average single fiber diameter Db of the second thermoplastic resin fiber to the average single fiber diameter Da of the first thermoplastic resin fiber is 1.0 or more, and the nonwoven fabric layer (B) is laminated on at least one of the outermost layers. The components are described in detail below.

[0019] [Thermoplastic resin fiber] The laminated nonwoven fabric of the present invention comprises a nonwoven fabric layer (A) made of a first thermoplastic resin fiber and a nonwoven fabric layer (B) made of a second thermoplastic resin fiber.

[0020] In the first thermoplastic resin fiber and the second thermoplastic resin fiber, the term "thermoplastic resin fiber" refers to a fiber made of a thermoplastic resin. Such a thermoplastic resin may be one type or may be made of multiple thermoplastic resins.

[0021] Examples of thermoplastic resins that can be used in the thermoplastic resin fiber according to the present invention include aromatic polyester-based polymers and copolymers thereof, such as "polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyhexamethylene terephthalate," aliphatic polyester-based polymers and copolymers thereof, such as "polylactic acid, polyethylene succinate, polybutylene succinate, polybutylene succinate adipate, polyhydroxybutyrate-polyhydroxyvalerate copolymer, polycaprolactone," aliphatic polyamide-based polymers and copolymers thereof, such as "polyamide 6, polyamide 66, polyamide 610, polyamide 10, polyamide 12, polyamide 6-12," polyolefin-based polymers and copolymers thereof, such as "polypropylene, polyethylene, polybutene, polymethylpentene," water-insoluble ethylene-vinyl alcohol copolymer-based polymers containing 25 mol % to 70 mol % ethylene units, polystyrene-based, polydiene-based, chlorine-based, polyolefin-based, polyester-based, polyurethane-based, polyamide-based, and fluorine-based elastomer polymers, and the like. The thermoplastic resin may be selected from the above. The above polymer may contain various additives such as inorganic substances such as titanium oxide, silica, and barium oxide, colorants such as carbon black, dyes, and pigments, flame retardants, fluorescent brighteners, antioxidants, and ultraviolet absorbing agents.

[0022] At least a part of the thermoplastic resin used in the thermoplastic resin fiber according to the present invention preferably contains a fatty acid amide compound. The content of the fatty acid amide compound is preferably 0.5% by mass or more, more preferably 0.7% by mass or more, and even more preferably 1.0% by mass or more, so that the fatty acid amide compound acts as a lubricant on the fiber surface, and a laminated nonwoven fabric with excellent touch can be obtained. The upper limit of the content of the fatty acid amide compound in the present invention is not particularly limited, but is preferably 5.0% by mass or less from the viewpoint of cost and productivity.

[0023] In the present invention, the content of the fatty acid amide compound in the thermoplastic resin is preferably 0.5 to 5.0 mass %, more preferably 0.7 to 5.0 mass %, and further preferably 1.0 to 5.0 mass %.

[0024] When the thermoplastic resin used in the thermoplastic resin fiber according to the present invention contains the fatty acid amide compound, the fatty acid amide compound preferably has a carbon number of 15 to 50. Examples of fatty acid amide compounds having a carbon number of 15 to 50 include saturated fatty acid monoamide compounds, saturated fatty acid diamide compounds, unsaturated fatty acid monoamide compounds, and unsaturated fatty acid diamide compounds. In the present invention, the carbon number means the number of carbon atoms contained in the molecule. Specific examples of the fatty acid amide compound include palmitic acid amide, palmitoleic acid amide, stearic acid amide, oleic acid amide, elaidic acid amide, vaccenic acid amide, linoleic acid amide, linolenic acid amide, pinolenic acid amide, eleostearic acid amide, stearidonic acid amide, bosseopentaenoic acid amide, arachidic acid amide, gadoleic acid amide, eicosenoic acid amide, eicosadienoic acid amide, mead acid amide, eicosatrienoic acid amide, arachidonic acid amide, eicosatetraenoic acid amide, eicosapentaenoic acid amide, henicosyl acid amide, behenic acid amide, erucic acid amide, docosadienoic acid amide, adrenic acid amide, osbondoic acid amide, sardine acid amide, docosahexaenoic acid amide, and lignocerin. Examples of the fatty acid amide include amide, nervonic acid amide, tetracosapentaenoic acid amide, nisinic acid amide, cerotic acid amide, montanic acid amide, melissic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, methylene bislauric acid amide, ethylene bisstearic acid amide, ethylene bisoleic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, ethylene biserucic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene hydroxystearic acid amide, distearyl adipic acid amide, distearyl sebacic acid amide, and hexamethylene bisoleic acid amide, and a combination of these can be used. By making the carbon number of the fatty acid amide compound preferably 15 or more, more preferably 23 or more, and even more preferably 30 or more, it is possible to suppress excessive precipitation of the fatty acid amide compound on the fiber surface, and to achieve excellent spinnability and processing stability and high productivity.In addition, by setting the carbon number of the fatty acid amide compound to preferably 50 or less, more preferably 45 or less, and even more preferably 42 or less, the fatty acid amide compound is appropriately precipitated on the fiber surface, resulting in a laminated nonwoven fabric with excellent touch. The carbon number of the fatty acid amide compound is preferably 15 to 50, more preferably 23 to 45, and even more preferably 30 to 42.

[0025] The first thermoplastic resin fibers and the second thermoplastic resin fibers may be made of the same or different thermoplastic resins.

[0026] [First nonwoven fabric layer (A) made of thermoplastic resin fibers] The nonwoven fabric layer (A) in the laminated stretch nonwoven fabric of the present invention is made of the above-mentioned first thermoplastic resin fibers, and the cross section of these first thermoplastic resin fibers has a plurality of convex portions.

[0027] The cross section of the fiber having a plurality of convex ridges as referred to herein means a cross section shape as described below, which will be explained with reference to FIG.

[0028] An example of a fiber cross section having multiple convex portions is shown in Figure 1. In this fiber cross section, the cross-sectional shape refers to a straight line passing through two points (S11, S12) on the contour (C1) of the cross section, where at least two lines (e.g., L11) can be drawn that do not pass through the contour (C1) between S11 and S12.

[0029] The above-mentioned cross-sectional shape is a fiber cross-section having a plurality of convex portions. By forming such a fiber cross-section, continuous grooves are formed on the fiber side in the fiber axis direction. The fiber cross-section having a plurality of convex portions is one of the key elements for achieving the effects of the present invention. That is, when such fibers are formed into a nonwoven fabric, the grooves on the fiber side become liquid passages, making it possible to diffuse moisture in the nonwoven fabric surface direction, which was previously difficult. Therefore, in the laminated nonwoven fabric of the present invention, by including a nonwoven fabric layer (A) capable of diffusing moisture in the surface direction, the water absorption rate and liquid migration from the surface layer can be significantly improved.

[0030] In order to make this water diffusion effect in the plane direction significant, the shape of the convex parts of the fiber cross section is important, and it is also important that the fiber cross section has a modified cross section with a lobulity of 5.0% or more.

[0031] The degree of globalization of the fiber cross section is measured by the method described below, and will be described in detail with reference to FIG.

[0032] FIG. 2 shows an example of a cross section of the fibers constituting the nonwoven fabric layer (A) of the laminated nonwoven fabric of the present invention.

[0033] First, an image of the cross section of the fiber constituting the nonwoven fabric layer (A) is taken with a scanning electron microscope (SEM) at a magnification where a single fiber can be observed. Using the taken fiber cross-sectional image, a line (e.g., L21 in FIG. 2) is drawn that passes through two points (S21, S22 in FIG. 2) on the contour (C2 in FIG. 2) of the cross section within the same cross section, and the line segment between S21 and S22 does not pass through the contour (C2), and the distance a (unit: μm) between points S21 and S22 is measured. Next, a line (e.g., L22) is drawn that is parallel to the line (L21) and has only one intersection point (V21) between points S21 and S22 on the contour (C2). Then, the distance b (unit: μm) between this line (L21) and the line (L22) is measured. Furthermore, the percentage of the ratio of b to a (b / a×100, unit: %) is calculated. The same operation is carried out for 20 different fibers, the results of which are simply averaged, and the value is rounded off to one decimal place to obtain the globality referred to in the present invention.

[0034] A higher value of the global degree indicates that the fiber has deeper grooves on the side surface. Since a higher global degree increases the effect of diffusing moisture in the surface direction when the nonwoven fabric is made, a more preferred range of global degree is 10.0% or more. In order to suppress peeling of the protrusions due to friction during production and to obtain the laminated nonwoven fabric of the present invention with good quality, the global degree is more preferably 60% or less. Even more preferably, the global degree is 10 to 60%.

[0035] The first thermoplastic resin fiber constituting the nonwoven fabric layer (A) of the present invention has a plurality of convex portions in a cross section, and the cross section has a globality of 5.0% or more. The shape of the convex portions and the number of convex portions per fiber of the first thermoplastic resin constituting the nonwoven fabric layer (A) of the present invention are not limited.

[0036] From the viewpoint of fully utilizing the effect of diffusing moisture in the nonwoven fabric surface direction by the grooves on the fiber side, the average single fiber diameter of the first thermoplastic resin fiber constituting the nonwoven fabric layer (A) is preferably 1.0 to 25.0 μm. Furthermore, from the viewpoint of improving the water absorption performance by the capillary effect by densifying the nonwoven fabric layer, the average single fiber diameter of the first thermoplastic resin fiber is more preferably 20.0 μm or less. The average single fiber diameter of the first thermoplastic resin fiber constituting the nonwoven fabric layer (A) is even more preferably 1.0 to 20.0 μm.

[0037] The average single fiber diameter is determined as follows.

[0038] Using the image taken to measure the globality of the fiber cross section described above, the area Af formed by the cross-sectional contour of the single fiber is measured using image analysis software (such as "WinROOF2015" manufactured by Mitani Shoji Co., Ltd.), and the diameter of a perfect circle having the same area as this area Af is calculated. This is measured for 20 single fibers randomly extracted from the same nonwoven fabric layer, and a simple number average is calculated. The unit is μm, and the value rounded off to one decimal place is the average single fiber diameter referred to in the present invention.

[0039] [Nonwoven fabric layer (B) made of second thermoplastic resin fibers] The nonwoven fabric layer (B) in the laminated stretch nonwoven fabric of the present invention is composed of the above-mentioned thermoplastic resin fibers. The thermoplastic resin fibers constituting the nonwoven fabric layer (B) of the present invention may be either single component fibers or composite fibers.

[0040] The shape of the fiber cross section can be freely selected as long as it does not impair the effects of the present invention. A preferred fiber cross section is a circular cross section. By making the fiber cross section a circular cross section, the inter-fiber voids of the nonwoven fabric layer (B) can be expanded, improving liquid permeability.

[0041] From the viewpoint of liquid permeability, the average single fiber diameter of the second thermoplastic resin fibers constituting the nonwoven fabric layer (B) is preferably 3.0 to 30.0 μm. Furthermore, from the viewpoint of improving the surface feel when used as a sanitary material, the average single fiber diameter of the second thermoplastic resin fibers is more preferably 25.0 μm or less, and even more preferably 3.0 to 25.0 μm.

[0042] [Average single fiber diameter of nonwoven fabric layer (A) and nonwoven fabric layer (B)] In the laminated nonwoven fabric of the present invention, the ratio of the average single fiber diameter Db of the second thermoplastic resin fibers constituting the nonwoven fabric layer (B) to the average single fiber diameter Da of the first thermoplastic resin fibers constituting the nonwoven fabric layer (A) (Db / Da, hereinafter sometimes simply referred to as the average single fiber diameter ratio) is 1.0 or more.

[0043] Images of the cross sections of the fibers constituting the nonwoven fabric layer (A) and the nonwoven fabric layer (B) were taken with a scanning electron microscope (SEM) at a magnification at which one single fiber could be observed, and the average single fiber diameter Da of the first thermoplastic resin fiber constituting the nonwoven fabric layer (A) and the average single fiber diameter Db of the second thermoplastic resin fiber constituting the nonwoven fabric layer (B) were measured. The average single fiber diameter ratio is the ratio (Db / Da) of the average single fiber diameter Da of the first thermoplastic resin fiber constituting the nonwoven fabric layer (A) to the average single fiber diameter Db of the second thermoplastic resin fiber constituting the nonwoven fabric layer (B), and is a value rounded off to one decimal place.

[0044] In general, in a nonwoven fabric, the size of the voids between the fibers changes depending on the average single fiber diameter of the fibers that compose the fabric. Therefore, when nonwoven fabric layers with different average single fiber diameters are stacked, the nonwoven fabric layers have different interfiber void sizes, and when moisture adheres to the nonwoven fabric, the difference in capillary effect allows the moisture absorbed in the nonwoven fabric layer made of thick fibers to be quickly transferred to the nonwoven fabric layer made of thin fibers.

[0045] In order for this capillary effect to work and for good water absorption performance to be obtained, the ratio of average single fiber diameters (Db / Da) is 1.0 or more, and preferably 1.2 or more.

[0046] [Laminated nonwoven fabric] The laminated nonwoven fabric of the present invention is a laminated nonwoven fabric in which at least one layer each of the nonwoven fabric layer (A) and the nonwoven fabric layer (B) is laminated, and the nonwoven fabric layer (B) is laminated as the outermost layer of at least one of the layers.

[0047] By laminating the nonwoven fabric layer (B) having a large average single fiber diameter and large inter-fiber voids within the nonwoven fabric layer as the outermost layer, when moisture adheres to the nonwoven fabric layer (B) side, the moisture is quickly transferred to the nonwoven fabric layer (A), thereby achieving quick-drying properties on the outermost surface of the nonwoven fabric layer (B).

[0048] The laminated nonwoven fabric of the present invention preferably has a water absorption speed measured from at least one surface of 20 seconds or less.

[0049] The water absorption rate is measured based on "7.1.1 Dropping Method" of JIS L1907:2010 "Testing Method for Water Absorption of Textile Products." A single drop of water is dropped onto the laminated nonwoven fabric, and the time it takes for the water to be absorbed and for the mirror reflection on the surface to disappear is measured. The simple average of the values ​​measured at 10 different points is calculated, and the value is rounded off to the first decimal place in seconds to determine the water absorption rate.

[0050] A water absorption speed of 20 seconds or less indicates a good performance in removing water adhering to the surface, and a water absorption speed of 10 seconds or less is more preferable.

[0051] The basis weight of the laminated nonwoven fabric of the present invention is 10 to 100 g / m 2 It is preferable to set the above.

[0052] The basis weight is preferably 10 g / m 2 More preferably, 13 g / m 2 More preferably, 15 g / m 2 By adjusting the weight to 100 g / m or more, a laminated nonwoven fabric having a mechanical strength sufficient for practical use can be obtained. 2 Less than 50 g / m 2 By setting the following, it is possible to obtain a laminated nonwoven fabric having an appropriate flexibility suitable for use as a nonwoven fabric for sanitary materials. The basis weight of the laminated nonwoven fabric of the present invention is preferably 13 to 50 g / m 2 It is.

[0053] Laminated nonwoven fabric weight (g / m 2 ) is based on "6.2 Mass per unit area" of JIS L1913:2010 "General nonwoven fabric test method", 20cm x 25cm test pieces are taken, 3 pieces per 1m of sample width, and the mass (g) of each is measured under standard conditions, and the mass per unit area is calculated from the average value. 2 Refers to the mass per unit.

[0054] In the laminated nonwoven fabric of the present invention, the nonwoven fabric layer (A) and the nonwoven fabric layer (B) are preferably integrated together. The term "integrated" as used herein means that these layers are bonded together by entanglement of the fibers, fixation with an adhesive or other component, or fusion of the thermoplastic resins constituting each layer.

[0055] The laminated nonwoven fabric of the present invention may be provided with a hydrophilic agent in order to increase water absorbency.

[0056] [Hygiene materials] The sanitary material of the present invention is at least partially composed of the laminated nonwoven fabric. The sanitary material of the present invention has excellent water absorption and excellent quick-drying properties. The sanitary material of the present invention is mainly a disposable article used for health-related purposes such as medical care and nursing. Examples of the sanitary material of the present invention include disposable diapers, sanitary napkins, gauze, bandages, masks, gloves, bandages, etc., and also include components thereof, such as top sheets, back sheets, side gathers, etc. of disposable diapers. Among them, the following embodiments are preferred.

[0057] A first preferred embodiment of the sanitary material of the present invention is a diaper having a top sheet made of the above-mentioned laminated nonwoven fabric. In particular, when the above-mentioned laminated nonwoven fabric is used so that the nonwoven fabric layer (B) is placed as the skin-facing side of the top sheet of the diaper, it quickly absorbs excreted urine and the liquid is quickly transferred to the nonwoven fabric layer (A), so that the surface of the laminated nonwoven fabric can be kept dry.

[0058] A second preferred embodiment of the sanitary material of the present invention is a mask whose inner layer is made of the laminated nonwoven fabric. The inner layer in the present invention refers to the layer of the facepiece that covers the mouth and is placed closest to the mouth. When the laminated nonwoven fabric is used so that the nonwoven fabric layer (B) is placed on the skin side, even if sweat or breath condenses and moisture adheres to the skin side, it is quickly absorbed inside the laminated nonwoven fabric, and the skin side can be kept dry, so that there is no discomfort when worn, and this is a preferred use.

[0059] [Manufacturing method of laminated nonwoven fabric] Next, a preferred embodiment for producing the laminated nonwoven fabric of the present invention will be specifically described.

[0060] The method for producing the nonwoven fabric layer (A) and the nonwoven fabric layer (B) constituting the laminated nonwoven fabric of the present invention can be selected from known production methods such as the spunbond method, the meltblowing method, and the staple fiber carding method.

[0061] Among these, the spunbond method is preferred because of its excellent productivity.

[0062] A preferred embodiment for producing the laminated nonwoven fabric of the present invention based on the spunbonding method will be described below, but the present invention is not limited thereto.

[0063] The spunbond method is a method for producing nonwoven fabrics in which a thermoplastic resin raw material is melted, spun from a spinneret, cooled and solidified to produce threads, which are then pulled and stretched by an ejector, collected on a moving net to form a nonwoven fiber web, and then thermally bonded.

[0064] In the spunbonding method, various shapes of spinnerets and ejectors can be used, such as round and rectangular shapes. Among them, it is preferable to use a combination of a rectangular spinneret and a rectangular ejector, from the viewpoints that the amount of compressed air used is relatively small and fusion or abrasion between the yarns is unlikely to occur.

[0065] Furthermore, by changing the shape of the polymer discharged from the spinneret, the shape of the fiber cross section can be controlled, which is preferable for producing the nonwoven fabric layer (A) in the laminated nonwoven fabric of the present invention.

[0066] When producing the laminated nonwoven fabric of the present invention, the spinning temperature is preferably set to (melting temperature of the thermoplastic resin as raw material + 10°C) or more and (melting temperature of the thermoplastic resin as raw material + 100°C) or less. By setting the spinning temperature within the above range, a stable molten state can be achieved, and excellent spinning stability can be obtained.

[0067] The spun yarn is then cooled. Examples of methods for cooling the spun yarn include a method of forcibly blowing cold air onto the yarn, a method of naturally cooling the yarn at the ambient temperature around the yarn, and a method of adjusting the distance between the spinneret and the ejector. Alternatively, a combination of these methods can be used. The cooling conditions can be appropriately adjusted in consideration of the discharge rate per hole of the spinneret, the spinning temperature, the ambient temperature, and the like.

[0068] Next, the cooled and solidified yarn is pulled and stretched by compressed air jetted from an ejector.

[0069] In the laminated nonwoven fabric of the present invention, it is important to control the average single fiber diameter of the fibers constituting the nonwoven fabric layer (A) and the nonwoven fabric layer (B).

[0070] The average single fiber diameter of the fiber is determined by the output per nozzle of the spinneret and the drawing speed, i.e., the spinning speed, and therefore it is preferable to determine the output and spinning speed according to the desired average single fiber diameter.

[0071] The spinning speed is preferably 2000 m / min or more, more preferably 3000 m / min or more. By setting the spinning speed at 2000 m / min or more, high productivity is achieved, and the orientation and crystallization of the fibers progresses, making it possible to obtain long fibers with high strength.

[0072] The filamentary yarn thus drawn by towing is collected on a moving net and made into a sheet, which is then subjected to a thermal bonding step.

[0073] The laminated nonwoven fabric of the present invention is a laminated nonwoven fabric obtained by laminating at least one layer each of the nonwoven fabric layer (A) and the nonwoven fabric layer (B). As a method for laminating the two nonwoven fabric layers, for example, a method of continuously collecting a nonwoven fabric layer obtained by collecting a second thermoplastic resin fiber by a spunbonding method on a nonwoven fabric layer obtained by collecting a first thermoplastic resin fiber on a collecting net by a spunbonding method in-line and laminating them together, a method of overlapping the nonwoven fabric layer (A) and the nonwoven fabric layer (B) obtained separately offline and laminating them together by thermocompression bonding, etc. can be adopted. Among them, the method of continuously collecting a nonwoven fabric layer obtained by collecting a second thermoplastic resin fiber by a spunbonding method on a nonwoven fabric layer obtained by collecting a first thermoplastic resin fiber on a collecting net by a spunbonding method in-line and laminating them together by thermal bonding is preferable because it has excellent productivity.

[0074] Methods for laminating and integrating the laminated nonwoven fabric of the present invention by thermal bonding can include thermal bonding methods using various rolls, such as a thermal embossing roll consisting of a pair of upper and lower rolls, each of which has an engraving (uneven portion) on its surface, a thermal embossing roll consisting of a combination of a roll with one flat (smooth) surface and a roll with an engraving (uneven portion) on the surface of the other roll, and a thermal calendar roll consisting of a pair of upper and lower flat (smooth) rolls, as well as thermal compression bonding methods such as ultrasonic bonding in which the fabric is thermally welded by the ultrasonic vibration of a horn.

[0075] When the laminated nonwoven fabric of the present invention is produced by thermocompression bonding, the multiple nonwoven fabric layers are sufficiently bonded together, and the mechanical strength of the laminated nonwoven fabric is increased, which is preferable.

[0076] On the other hand, as a method for laminating and integrating the laminated nonwoven fabric of the present invention by thermal bonding, there can also be mentioned a so-called air-through method, which is a method for blowing hot air.

[0077] When the laminated nonwoven fabric of the present invention is produced by this air-through method, it is preferred because it has a high bulk and an excellent feel.

[0078] In the laminated nonwoven fabric of the present invention, it is sufficient that the nonwoven fabric layer (B) is laminated on at least one surface layer, and the number and combination of layers can be arbitrarily selected depending on the purpose. EXAMPLES

[0079] Next, the present invention will be described in detail based on examples. However, the present invention is not limited to these examples. In addition, in the measurement of each physical property, unless otherwise specified, the measurement was performed based on the above-mentioned method.

[0080] (1) Globalization of fiber cross section Single fiber samples were randomly taken from the nonwoven fiber web collected on a net, and images of the fiber cross sections were taken using a Hitachi High-Technologies Corporation scanning electron microscope (SEM) "S-5500" at a magnification sufficient to observe a single fiber.

[0081] (2) Ratio of the average single fiber diameter Db of the second thermoplastic resin fiber to the average single fiber diameter Da of the first thermoplastic resin fiber (Db / Da) The image analysis software used was "WinROOF2015" manufactured by Mitani Shoji Co., Ltd.

[0082] (3) Water absorption rate The water absorption rate was measured based on "7.1.1 Dropping Method" of JIS L1907:2010 "Testing Method for Water Absorption of Textile Products." A single drop of water was dropped onto the laminated nonwoven fabric, and the time it took for the water to be absorbed and for the mirror reflection on the surface to disappear was measured. The simple average of the values ​​measured at 10 different points was calculated, and the unit was seconds, rounded off to the first decimal place.

[0083] (4) Water absorption and quick drying properties In the laminated nonwoven fabric, one drop of water was dropped on the surface of the nonwoven fabric layer (B), and after one minute, healthy adults (15 men and 15 women, total of 30 people) touched the surface with their hands and evaluated it on the following three-point scale. The average score of the evaluation results for each nonwoven fabric was calculated and used as the feel of the laminated nonwoven fabric. 5: The surface is dry and there is no moisture. 3: There is no moisture on the surface, but it is moist. 1: The surface is moist and moist.

[0084] [Example 1] (Nonwoven fabric layer (A)) Polypropylene (PP) was melted in an extruder and spun into hexa-lobe cross-section fibers from a rectangular die at a single-hole output rate of 0.56 g / min. The spun yarn was cooled and solidified, then pulled and stretched in a rectangular ejector with compressed air at an ejector pressure of 0.08 MPa, and collected on a moving net to obtain a nonwoven fiber web. The characteristics of the fibers constituting the obtained spunbond nonwoven fabric layer (A) were an average single fiber diameter of 15.5 μm and a globality of 8.8.

[0085] (Nonwoven fabric layer (B)) Polypropylene (PP) was melted in an extruder and spun into circular cross-section fibers from a rectangular die with a hole diameter of 0.4 mm at a single hole output rate of 0.90 g / min. The spun yarn was cooled and solidified, then pulled and stretched in a rectangular ejector with compressed air at an ejector pressure of 0.10 MPa, and collected on a moving net to obtain a nonwoven fiber web. The characteristics of the fibers constituting the obtained spunbond nonwoven fabric layer (B) were an average single fiber diameter of 20.4 μm.

[0086] (Laminated nonwoven fabric) Nonwoven fabric layer (B) was collected directly on top of the nonwoven fabric layer (A) obtained above (the lamination method is indicated as "in-line" in Table 1), thereby obtaining a laminated fiber web having a two-layer structure of a spunbond nonwoven fabric layer-spunbond nonwoven fabric layer (the lamination structure is indicated as "A / B" in Table 1).

[0087] The laminated fiber web thus obtained was heat-bonded at a line pressure of 300 N / cm and a heat bonding temperature of 125°C using a metal embossing roll on the upper roll, in which circular convex portions are staggered at the same pitch in both MD and CD directions, and a metal flat roll on the lower roll, which is a pair of embossing rolls having upper and lower heating mechanisms, to obtain a web having a basis weight of 40 g / m. 2 Thus, a laminated nonwoven fabric was obtained.

[0088] The obtained laminated nonwoven fabric was subjected to hydrophilic treatment, and then the average single fiber diameter ratio, water absorption rate, and water absorption and quick-drying property were evaluated. The results are shown in Table 1.

[0089] [Example 2] A laminated nonwoven fabric was obtained in the same manner as in Example 1, except that the fiber cross section of nonwoven fabric layer A was made trilobal. The evaluation results of the obtained laminated nonwoven fabric are shown in Table 1.

[0090] [Example 3] A laminated nonwoven fabric was obtained in the same manner as in Example 1, except that the single-hole output rate was 0.65 g / min in the production method for nonwoven fabric layer B. The evaluation results of the obtained laminated nonwoven fabric are shown in Table 1.

[0091] [Example 4] The fibers of the nonwoven fabric layer (A) were collected on a conveyor in the same manner as in Example 1, and thermally bonded in the same manner as in Example 1 to obtain a nonwoven fabric layer (A). Similarly, the fibers of the nonwoven fabric layer (B) were collected on a conveyor in the same manner as in Example 1, and thermally bonded in the same manner as in Example 1 to obtain a nonwoven fabric layer (B). The nonwoven fabric layer (A) and the nonwoven fabric layer (B) thus obtained were laminated (the lamination method is described as "offline" in Table 1), and thermally bonded in the same manner as in Example 1 to obtain a laminated nonwoven fabric. The evaluation results of the obtained laminated nonwoven fabric are shown in Table 1.

[0092] [Example 5] The polymer used for the nonwoven fabric layer (A) and the nonwoven fabric layer (B) was polyethylene glycol copolymerized polyethylene terephthalate (copolymerized PET, the copolymerization rate of polyethylene glycol was 8% by mass of the polymer).

[0093] (Nonwoven fabric layer (A)) Except for using copolymerized PET as the polymer, a nonwoven fiber web was obtained in the same manner as in Example 1. The characteristics of the fibers constituting the obtained spunbonded nonwoven fabric layer (A) were an average single fiber diameter of 12.5 μm and a global index of 22.2.

[0094] (Nonwoven fabric layer (B)) Except for using copolymerized PET as the polymer, a nonwoven fiber web was obtained in the same manner as in Example 1. The characteristics of the fibers constituting the obtained spunbonded nonwoven fabric layer (B) were that the average single fiber diameter was 16.9 μm.

[0095] (Laminated nonwoven fabric) A laminated nonwoven fabric was obtained in the same manner as in Example 1, except that the heat bonding temperature was 200° C. The evaluation results of the obtained laminated nonwoven fabric are shown in Table 2.

[0096] [Example 6] A nonwoven fabric layer (A) was collected on top of the nonwoven fabric layer (C) described below in the same manner as in Example 1, and a nonwoven fabric layer (B) was collected on top of that, and the layers were thermally bonded in the same manner as in Example 1 to obtain a laminated nonwoven fabric (in Table 2, the laminated structure is indicated as "C / A / B"). The evaluation results of the obtained laminated nonwoven fabric are shown in Table 2.

[0097] (Non-woven fabric layer (C)) Polypropylene (PP) was melted in an extruder and spun into circular cross-section fibers from a rectangular die with a hole diameter of 0.4 mm at a single hole output rate of 0.65 g / min. The spun yarn was cooled and solidified, then pulled and stretched in a rectangular ejector with compressed air at an ejector pressure of 0.10 MPa, and collected on a moving net to obtain a nonwoven fiber web. The characteristics of the fibers constituting the obtained spunbond nonwoven fabric layer (C) were an average single fiber diameter of 16.0 μm.

[0098] [Comparative Example 1] A laminated nonwoven fabric was obtained in the same manner as in Example 1, except that the shape of the nozzle hole of the die used in the nonwoven fabric layer (A) was round. All of the fibers in the nonwoven fabric layer (A) had a round cross section, and it was not possible to measure the global degree. The evaluation results of the obtained laminated nonwoven fabric are shown in Table 2.

[0099] [Comparative Example 2] A laminated nonwoven fabric was obtained in the same manner as in Example 1, except that in the production method of the nonwoven fabric layer (B), the single-hole discharge rate was 0.55 g / min and the pressure in the ejector was 0.08 MPa. The fibers of the nonwoven fabric layer (B) had an average single fiber diameter of 15.0 μm. The evaluation results of the obtained laminated nonwoven fabric are shown in Table 2.

[0100] [Comparative Example 3] A nonwoven fabric layer (C) was formed on the nonwoven fabric layer (C) in the same manner as in Example 1. B ) is collected, and a nonwoven fabric layer ( A The nonwoven fiber web on which the particles were collected was thermally bonded in the same manner as in Example 1 to obtain a laminated nonwoven fabric (the laminate structure is indicated as "A / B / C" in Table 2). The evaluation results of the obtained laminated nonwoven fabric are shown in Table 2.

[0101] (Non-woven fabric layer (C)) Polypropylene (PP) was melted in an extruder and spun into circular cross-section fibers from a rectangular die with a hole diameter of 0.4 mm at a single hole output rate of 0.55 g / min. The spun yarn was cooled and solidified, then pulled and stretched in a rectangular ejector with compressed air at an ejector pressure of 0.08 MPa, and collected on a moving net to obtain a nonwoven fiber web. The characteristics of the fibers constituting the obtained spunbond nonwoven fabric layer (C) were an average single fiber diameter of 15.0 μm.

[0102] [Table 1]

[0103] [Table 2]

[0104] As shown in Tables 1 and 2, it is understood that Examples 1 to 6 are excellent in water absorption and quick drying properties. In particular, Examples 1, 5, and 6 achieved both high water absorption speed and water absorption and quick drying properties. On the other hand, Comparative Examples 1 to 3 showed low water absorption and quick drying properties. [Industrial Applicability]

[0105] The laminated nonwoven fabric of the present invention has a sufficient water absorption rate and water absorption and quick-drying properties to be used as a nonwoven fabric for sanitary materials. By using the laminated nonwoven fabric of the present invention as at least a part of a sanitary material, a sanitary material having excellent water absorption and excellent quick-drying properties can be obtained.

[0106] The laminated nonwoven fabric of the present invention can be used as a part of sanitary materials such as disposable diapers, sanitary napkins, gauze, bandages, masks, gloves, and adhesive bandages. [Explanation of symbols]

[0107] C1: Cross section contour L11: A straight line passing through two points (S11, S12) on the cross-sectional contour (C1) of the fiber cross section. S11, S12: points on the cross-sectional contour (C1) of the fiber cross section C2: Cross section contour L21: A straight line passing through two points (S21, S22) on the cross-sectional contour (C2) of the fiber cross section. L22: A line that is parallel to the straight line (L21) and has only one intersection point (V21) between points S21 and 22 on the contour (C2). S21, S22, V21: points on the cross-sectional contour (C2) of the fiber cross section a: Distance between points S21 and S22 b: The distance between line (L21) and line (L22)

Claims

1. A laminated nonwoven fabric for sanitary materials, comprising at least one layer each of a nonwoven fabric layer (A) made of a first thermoplastic resin fiber and a nonwoven fabric layer (B) made of a second thermoplastic resin fiber, wherein the cross section of the first thermoplastic resin fiber has a plurality of convex portions and is an irregular cross section having a globality of 5% or more, and a ratio (Db / Da) of an average single fiber diameter Db of the second thermoplastic resin fiber to an average single fiber diameter Da of the first thermoplastic resin fiber is 1.0 or more, and further wherein the nonwoven fabric layer (B) is at least one outermost layer and is laminated on the skin-facing side of the sanitary material.

2. 2. The laminated nonwoven fabric for sanitary materials according to claim 1, wherein the laminated nonwoven fabric has a water absorption rate measured from at least one surface thereof of 20 seconds or less.

3. A sanitary material, at least a part of which is composed of the laminated nonwoven fabric for sanitary materials according to claim 1 or 2.

4. A diaper, the top sheet of which is made of the laminated nonwoven fabric for sanitary materials according to claim 1 or 2.

5. A mask, the inner layer of which is made of the laminated nonwoven fabric for sanitary materials according to claim 1 or 2.

Citation Information

Patent Citations

  • Surface sheet of absorbable article

    JP1989020844A

  • Novel disposable sanitary material

    JP1989192803A

  • Bulky non-woven fabric being suitable for surface material of hygienic material

    JP1993031137A

  • Thermal stencil printing base sheet

    JP1997076656A

  • Two-layer structure cloth

    JP1997085872A